Exploring The Lexical and Contextual Meaning of The Word “Zauj” in Quranic Discourse - Iqbal Fathi Izzudin; Muhammad Lukman Arifianto; Zulfa Azalia Mujahidah; Moh. Fery Fauzi (Al-Arabi: Jurnal Bahasa Arab dan Pengajarannya = Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2023)
Qur'an is the holy book of Muslims that contains religious teachings and serves as a guide to the life of all Muslims who demand to be studied and understood. One way to understand the meaning of the verse of the Qur'an is to study it from the point of view of semantics, especially the lexical and contextual meaning of the words that compose the verse. One of the words that is important to study its meaning is the word "Zauj" which is mentioned a lot in the Qur'an and has dimensions of meaning that vary depending on the context of the sentence. This paper aims to examine the dimensions of the contextual meaning of the word "Zauj" in the Qur'an from the point of view of semantics, determine what meanings the word "Zauj" has, and prove that the word is polysemous. By relying on literature studies related to studies on the meaning of the word "Zauj" in the Qur'an, the dimensions of the lexical and contextual meaning of this word can be mapped out well. After examining the word "Zauj" which is mentioned 70 times in the Qur'an, it can be noted that there is a polysemy of meaning in the word. The results showed that the word "Zauj" has several meanings, they are 1) Husband, 2) Wife, 3) Type or Group, 4) Male and Female Pair, and 5) Allies or Partners. This result implies that one word in Arabic (al-Quran) can have several meanings based on the context of the verse or sentence that accompanies it, so it is necessary to consider the context of the speech accurately when translating a word or sentence.